Loka: A Cross-Platform Virtual Reality Streaming Framework for the Metaverse - Hsiao-Wen Kao; Yan-Cyuan Chen; Eric Hsiao-Kuang Wu; Shih-Ching Yeh; Shih-Chun Kao (Sensors)
As the concept of the Metaverse evolves, virtual reality (VR) plays a pivotal role in creating immersive, socially interactive environments that form the backbone of this interconnected digital universe. However, VR technology often faces significant challenges, including hardware limitations, platform incompatibilities, and difficulties supporting seamless multiplayer experiences. VR streaming offers a potential solution by offloading computational tasks to remote servers, enabling high-quality VR experiences on lower-end devices and enhancing accessibility to a broader audience. In this paper, we present Loka, a versatile and extensible VR streaming framework designed to address these challenges, providing the necessary infrastructure to support social interactions and real-time collaboration in virtual environments—the key components of the Metaverse. Loka is built on Unity Engine and WebRTC, enabling seamless cross-platform VR experiences without the need for device-specific SDKs. It also supports real-time integration of custom sensory data streams, such as motion capture and physiological signals from IoT devices, which can enhance user interaction and personalization in virtual environments, as well as provide a more convenient accessible platform for research. Furthermore, Loka’s native multiplayer and multicasting capabilities facilitate collaborative and interactive social experiences, aligning with the core goals of the Metaverse. By leveraging cloud-based rendering with low-latency streaming, Loka allows users to engage in immersive VR environments on a wide range of devices, without requiring high-end hardware. Its modular architecture ensures extensibility, allowing researchers and developers to integrate new data types and experimental setups more easily. With its ability to set up immersive VR scenes to support social interaction and handle complex virtual environments, we believe the proposed work can be leveraged to foster the development and research of the Metaverse.